Ticagrelor-based antiplatelet regimens in patients with atherosclerotic artery disease—A meta-analysis of randomized clinical trials - Cassese, Salvatore; Ndrepepa, Gjin; Byrne, Robert A.; Laugwitz, Karl-Ludwig; Schunkert, Heribert; Fusaro, Massimiliano; Alfonso, Fernando; Kastrati, Adnan (American Heart Journal, 2020)
Background: Randomized trials did not consistently support superiority of ticagrelor, as monotherapy or in combination with aspirin, in terms of efficacy or safety, in patients with atherosclerotic artery disease. Methods: Medline, EMBASE, the Cochrane Central Register of Controlled Trials, and scientific session abstracts were searched for trials of patients with coronary or peripheral artery disease (with >1,000 participants and a follow-up ≥3 months) randomly assigned to ticagrelor-based or conventional antiplatelet therapies. Trial-level hazard ratios (HRs) were pooled using a fixed- or random-effect model (in case of significant heterogeneity) with the inverse variance weighting. The primary outcome was all-cause mortality. Other outcomes were myocardial infarction (MI), stroke, and major bleeding. Results: Overall 77,489 patients received either ticagrelor-based (n = 38,721) or conventional antiplatelet regimens (n = 38,768) in 6 trials. The primary outcome occurred in 4.5% of patients treated with experimental therapy and 4.9% of patients treated with control therapy (HR = 0.91, 95% CI 0.81-1.01; P =.07). Overall, patients treated with ticagrelor-based versus conventional antiplatelet regimens showed no significant difference in terms of all-cause death, MI, stroke, or major bleeding after 20 months. However, in trials of patients with coronary artery disease as primary diagnosis, the risk for all-cause death (HR = 0.84 [0.77-0.91], P <.001) and MI (HR = 0.87 [0.80-0.94], P =.007) was significantly reduced by experimental therapy. Conclusions: In patients with atherosclerotic artery disease, the benefit of ticagrelor-based therapies was confined to patients treated for coronary artery disease. The drug significantly reduced the risk for all-cause death and MI without excess risk of bleeding in these patients. In consideration of limitations of subgroup analyses, these results need further validation.
CRIS-Team Scopus Importer:2023-03-08